Membentuk kepribadian Islami generasi Z melalui pembelajaran akidah yang menarik - Lahitania, Zahra (Maliki Interdisciplinary Journal, 2024)
Generation Z, born in the digital era, possesses unique characteristics compared to previous generations. They have extensive access to information and high digital technology skills. In this context, an innovative approach to Aqeedah learning is necessary to shape a strong Islamic personality in this generation. This article highlights the urgency of engaging Aqeedah learning for Generation Z and proposes strategies such as utilizing digital technology, adopting an interactive approach, and providing contextual learning materials. Studies have shown that these approaches can enhance Generation Z’s understanding and practice of Aqeedah, strengthening their Islamic identity amidst the challenges of the digital age.